LED Phototherapy with Gelatin Sponge Promotes Wound Healing in Mice. (1st December 2017) - Zhang, Heng; Liu, Shupeng; Yang, Xiangfei; Chen, Na; Pang, Fufei; Chen, Zhenyi; Wang, Tingyun; Zhou, Jianshe; Ren, Fuji; Xu, Xiaoyin; Li, Taihao
Abstract: Tiny but highly efficient, a light‐emitting diode (LED) can power a therapy device, such as a phototherapy device, and, at the same time, decrease the device's size requirements. In this study, a LED phototherapy device was designed to investigate the possible impact on wound healing using a mouse model and a cell line exposed to red and blue light. To enhance wound phototherapy, a gelatin sponge was fabricated. Results showed that the red and blue lights promoted cell growth and wound healing, while the blue light with a gelatin sponge protected the wound from infection in the early stages of wound healing. The LED phototherapy device combined with the gelatin sponge, therefore, has potential significance in clinical application for wound healing. Abstract : A LED phototherapy device was designed to detect the possible effects for wound healing using a mouse model and a cell line exposed to red and blue light. To enhance the wound phototherapy, a gelatin sponge was fabricated and applied to the wound healing. Results showed that the red and blue light promoted cell growth and wound healing, while the blue light with a gelatin sponge protected the wound from infection in the early stages of wound healing. The LED phototherapy device combined with the gelatin sponge, therefore, has potential significance in clinical application for wound healing.